Smoking is a significant contributor to intraoperative blood loss in metastatic spinal tumor surgery: a propensity score analysis - Xuedong Shi; Yunpeng Cui; Bailin Wang; Yuanxing Pan; Bing Wang; Yong Qin; Mingxing Lei (BMC Cancer)
Abstract Background Metastatic spinal tumors pose a significant challenge regarding intraoperative blood loss. Identifying risk factors for intraoperative blood loss is crucial for appropriate surgical planning and early intervention. However, current studies have not comprehensively evaluated risk factors for predicting intraoperative blood loss. This study aims to determine whether smoking significantly contributes to intraoperative blood loss among metastatic spinal tumors and to investigate other potential risk factors. Methods This study analyzed 252 patients with metastatic spinal disease who underwent posterior decompressive surgery, and the primary outcome measured was intraoperative blood loss, with massive intraoperative blood loss defined as exceeding 2500 mL. Propensity score matching analysis was employed to analyze the influence of smoking on intraoperative blood loss. In addition, subgroup analysis was performed based on smoking status before and after propensity score analysis. Multivariate analysis was used to analyze the relationship between smoking and intraoperative blood loss. To assess the predictive value of smoking status for intraoperative massive blood loss, we conducted an analysis using the Area Under the Receiver Operating Characteristic Curve (AUROC), and the corresponding Area Under the Curve (AUC) values were subsequently calculated. Results Before conducting the propensity score analysis, the study found that smoking patients had a significantly higher volume of intraoperative blood loss (1938.30 mL vs. 1722.32 mL, P = 0.014) and a greater incidence of massive intraoperative blood loss (36.4% vs. 20.1%, P = 0.008) compared to non-smokers. After adjusting for propensity scores, the results showed that smokers still had a higher volume of intraoperative blood loss (1938.30 mL vs. 1703.41 mL, P = 0.019) and a higher proportion of massive intraoperative blood loss (39.7% vs. 14.9%, P = 0.002) than non-smokers. Multiple linear regression analysis confirmed that smoking status was significantly associated with intraoperative blood loss before (Estimate = 1.410, P = 0.001) and after (Estimate = 1.443, P = 0.010) propensity score matching analysis. Additionally, the logistic regression demonstrated that smokers were 2.268 times (95% CI: 1.272–4.044) more likely to experience intraoperative massive blood loss compared to nonsmokers before propensity score analysis (P = 0.005). After propensity score analysis, the fold increase in risk further rose to 3.764 (95% CI: 1.643–8.621), indicating an even stronger association between smoking and intraoperative blood loss (P = 0.002). Furthermore, the AUC value increased from 0.596 (95% CI: 0.527–0.666) for smoking status before propensity score matching analysis to 0.660 (95% CI: 0.567–0.753) after propensity score matching analysis. Conclusions Smoking is a significant risk factor for increased intraoperative blood loss and should be taken into consideration when planning surgical interventions for patients with metastatic spinal tumors.